HUKUM PERKONGSIAN (SYARIKAT) ANTARA MUSLIM DAN NON-MUSLIM - Mohamad, Shamsiah (Jurnal Syariah, 2019)
This article analyses the Islamic scholars' view towards business partnership between a muslim and a non-muslim. Certain /Uqaha' legitimatize such partnership, while other prohibit it. At the end, the writer gives her conclusion.